The perception of student towards book collections in PTDI, Segamat, Johor / Nuraini Zatuliyah Ab.Rahim - Ab.Rahim, Nuraini Zatuliyah (2014)
This study has investigated the perception of students towards book collections in PTDI, Segamat. It allocates to identify the understanding of student's perception toward book collections in order to improve and promote the usage of book collections among the users. There are that have been used for this study in order to explaining the operational definitions which are collected, collection development, book collections and academic library. This study includes the conceptual framework that defines as an organized, systematic, data based, critical, in order to investigate the problem happen. The theoretical framework acts as guidelines to determine the perceptions towards book collections. The population among students have been focused on this research. The conceptual framework acts as guidelines to determine the perceptions among students in PTDI. In completing the funding, have distributed the questionnaire to the target audiences. Lastly the findings that achievements have been correlated to the research.